Scanning tunneling microscopy of Ni and Fe nanocrystals on SrTiO3 - Rasheed, A (2019)
The equilibrium crystal shapes (ECS) of Ni and Fe were investigated on three different terminations of SrTiO3 {(001), (110), and (111)}. Firstly, to investigate surface reconstructions, SrTiO3 substrates were subjected to various thermal cycles. SrTiO3 is capable of producing a multitude of surface reconstructions such as (2 × 1), (2 × 2), (√5 × √5) R26.6°, and c(4 × 2) on (001) termination; (4 × 1) on (110) termination; and (4 × 4) and (6 × 6) on (111) termination. On SrTiO3 (001) sample, Ni grew itself in the form of a truncated pyramidal shape with (001) as the top facet, four (110) side facets and one (001) base facet. This shape of Ni nanocrystals was also observed on a SrTiO3 (001) sample that was subjected to sputtering followed by annealing at 920 ºC for 1 h. On SrTiO3 (110) sample, Ni grew itself in the form of truncated huts with (110) as the top facet, two (111) side facets, two (001) side facets, and one (110) base facet. On SrTiO3 (111) sample, Ni grew in two forms: icosahedron and truncated octahedron. Point, edge and face orientations of icosahedrons were observed. The icosahedron had (111) facets while truncated octahedron had (111) top facet, three (111) side facets, three (001) side facets, and one (111) base facet. On SrTiO3 (001) sample, Fe grew itself in the form of truncated pyramid shape with (001) as the top facet, four (110) side facets, and one (001) base facet. On another SrTiO3 (001) substrate, Fe grew in the form of truncated square-shaped and truncated rectangular-shaped nanocrystals. A surface texture was also observed and was found sensitive to tip bias. On SrTiO3 (110) sample, Fe grew itself in the form of truncated huts with (110) as the top facet, two (111) side facets, two (001) side facets, and one (110) base facet. On SrTiO3 (111) sample, Fe grew in two forms: truncated octahedron and truncated hut. Wulffman simulations of the nanocrystals were generated and adhesion energies were calculated.